Involvement of the Lung Parenchyma Analyzed by Frequency Components of the Tidal Volume Assessed by Electrical Bioimpedance - Vargas Luna, Francisco Miguel; Delgadillo Cano, María Isabel; Riu Costa, Pere Joan; Kashina, Svetlana; Balleza Ordaz, José Marco (Revista Mexicana de Ingenieria Biomedica, 2024)
Pulmonary function tests are vital for detecting pathologies, especially chronic obstructive pulmonary diseases (COPD), emphasizing the importance of assessing lung parenchyma involvement in maintaining proper gas exchange. Electrical impedance tomography (EIT) offers a non-invasive alternative for respiratory function evaluation while preserving natural breathing. We propose using EIT to detect lung parenchyma conditions by analyzing tidal volume patterns (by averaging the impedance image) in the frequency domain. Twenty COPD patients underwent simultaneous evaluation with a pneumotachometer and an EIT device, performing three 30-second respiratory maneuvers. FFT spectra analysis yielded parameters, including the area under the curve and quartiles (25 %, 50 %, 75 %) of power values in six frequency regions. Correlations between these parameters and clinical test results (pulmonary diffusing capacity and arterial blood gas analysis) revealed significant associations, particularly with PCO2. Multiple linear regression analysis predicted PCO2 with an R2adj = 0.827, suggesting the potential for non-invasively detecting lung parenchyma affectation by correlating FFT bioimpedance ventilatory patterns with gas exchange performance in COPD patients.